Konsumsi Pangan Sumber Zat Besi dan Asam Folat dengan Anemia pada Ibu Hamil di Puskesmas Tawaeli - Suastira; Sumiaty; Ansar (Jurnal Bidan Cerdas, 2018)
Anemia is a condition where the hemoglobin level in the blood is below normal. Anemia is directly caused by daily food intake that contains less iron and folic acid. Data from the Basic Health Research conducted in 2013 showed that the proportion of pregnant women who were anemic in Indonesia reached 37.1%, in Central Sulawesi anemia in pregnant women reached 24.42%, then for the Palu city it was found in the Tawaeli Health Center reaching 58, 7%. The purpose of this study was to determine the relationship between food consumption and folic acid with the incidence of anemia in pregnant women in the Tawaeli Health Center Area. This type of research is analytic observational using cross sectional. Sampling is done by visiting the respondent's place directly or door to door with 40 people. Data collection was done directly, using a food frequency questionnaire (FFQ) and to find out anemia in pregnant women using Hb meter (Diaspect). The results showed that the percentage of anemia anemia was higher in pregnant women who rarely discussed iron food (56.7%) with the results of statistical tests showing p value = 0.02 (p <0.05) and folic acid (52.6%) with the results of statistical tests showing a p value of 0.04 (p <0.05). The results showed an association between iron food and folic acid with the incidence of anemia in pregnant women.